Biopolitical Knowledge in the Making: Population Politics and Fertility Studies in Early Cold War Taiwan. Issue 4 (1st December 2016) - Huang, Yu-Ling
Abstract : Like many developing countries in the 1950s and 1960s, Taiwan experienced a social process of constructing and controlling population that relied on demography and fertility studies as essential governing tools. This article investigates population politics and biopolitical knowledge production in postwar Taiwan through synthesizing three bodies of literature that have just begun to comment on one another: histories of postwar population control, analyses of the technoscientific turn in Cold War history, and forensics into the production of social-scientific knowledge via science-study approaches. Along with the complexities of Asian biopolitics, three main social elements affecting the production of biopolitical knowledge at the time are discussed: (a) the historical backstage on which the Cold War and the civil war met, (b) the acting group of Taiwanese and US agencies and individuals who took part in the process, and (c) the three types of fertility studies and the data from them that ultimately expanded the focus of the process of population control from the population in general to the reproductive behavior of women. The complexities of Asia biopolitics are also discussed.